Dehumanization as a Response to Uncivil and Immoral Behaviors - Laura Rodríguez-Gómez; Naira Delgado; Armando Rodríguez-Pérez; Ramón Rodríguez-Torres; Verónica Betancor (MDPI AG, 2022)
Theoretical approaches to dehumanization consider civility to be an attribute of human uniqueness (HU). However, studies that explore the links between civility and humanness are scarce. More precisely, the present research tests whether there is a consistent relationship between civility and HU. Method and results: The first study (N = 192; Mage = 19.91; SD = 2.70; 69% women) shows that individuals infer more HU traits in the agents of civil behaviors compared to agents of other positive behaviors that are not related to civility. The second study (N = 328; Mage = 19.69; SD = 3.65; 77% women) reveals that uncivil and immoral behaviors displayed a similar pattern of inference of HU traits; however, moral behaviors were more associated with human nature than civil behaviors. Conclusions: Overall, results confirmed that civil behaviors facilitate the inference of humanness, specifically of HU traits, and that civil and moral behaviors are not equivalent in terms of the human inferences to which they lead.